La natura e il paesaggio in alcuni poeti ticinesi, da Giorgio Orelli a Fabio Pusterla e Antonio Rossi - Ippoliti, Francesca (L’ospite ingrato, 2021)
This article analyses representations of nature and landscape in Italian poetry from Italian Switzerland. After offering an overview of key theoretical concepts, I focus on two major authors in the canon, Giorgio Orelli and Fabio Pusterla, and develop some hypotheses about Antonio Rossi. By engaging with seminal contributions in the secondary literature and by close reading texts by the three aforementioned authors, I suggest that the relationship between nature and poetry in Italian Switzerland can be articulated into three phases: the Romantic phase, which goes until the first decades of 20th century; a second phase, which begins in the 1940s, as a result of the increasing number of exchanges with major Italian authors that defines the mid-twentieth century and in particular of Giorgio Orelli’s role as a mediator. A third, more recent phase, which is best exemplified by poets born in the 1950s, such as Fabio Pusterla and Antonio Rossi.